Peluang dan Tantangan Pemenuhan Hak Perempuan Pasca Cerai Gugat di Pengadilan Agama - Nurhasnah Nurhasnah (USRATY : Journal of Islamic Family Law, 2024)
Divorce is the dissolution of a marriage carried out through a court decision or at the request of one party in the marriage, often involving various legal and social considerations. PERMA No. 3 of 2017 concerning Guidelines for Judges in Adjudicating Cases Involving Women in Conflict with the Law serves as a legal foundation and an important reference for judges in the Religious Courts. This study employs the method of Empirical Legal Research, allowing the researcher to observe and evaluate the implementation of this regulation in the field. In addition to PERMA No. 3 of 2017, there are also supporting regulations such as SEMA No. 3 of 2018, SEMA No. 2 of 2019, and SEMA No. 5 of 2021. These regulations require judges to order the husband to pay maintenance to the wife before pronouncing the divorce declaration and issuing the divorce certificate. This aims to ensure that women's rights are protected and fulfilled, even in often complicated divorce situations. The research findings indicate that opportunities for fulfilling women's rights are increasingly open, creating legal equality based on the principle of justice and providing protection for women after divorce, which may not have been guaranteed previously. However, the lack of legal awareness from both parties, the husband and wife, has led to the implementation of these regulations not running efficiently and effectively. Therefore, this study is expected to contribute to the development of policies and legal practices that are more supportive of women in the divorce process.